2017
DOI: 10.1155/2017/3819246
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Phase Transitions and Triple Points of Topological AdS Black Holes in Born-Infeld-Massive Gravity

Abstract: The publication of this article was funded by SCOAP 3 .Motivated by recent developments of black hole thermodynamics in de Rham, Gabadadze, and Tolley (dRGT) massive gravity, we study the critical behaviors of topological Anti-de Sitter (AdS) black holes in the presence of Born-Infeld nonlinear electrodynamics.Here the cosmological constant appears as a dynamical pressure of the system and its corresponding conjugate quantity is interpreted as thermodynamic volume. This shows that, besides the Van der Waals-li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 101 publications
0
35
0
Order By: Relevance
“…Moreover, the small-large black hole phase transition was identified with the liquid-gas phase transition of Van der Waals (VdW) fluid [6]. Besides it, more interesting phase transitions were found [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In particular, near the critical point, black hole systems were also found to possess the same critical phenomena with the VdW fluid.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, the small-large black hole phase transition was identified with the liquid-gas phase transition of Van der Waals (VdW) fluid [6]. Besides it, more interesting phase transitions were found [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In particular, near the critical point, black hole systems were also found to possess the same critical phenomena with the VdW fluid.…”
Section: Introductionmentioning
confidence: 91%
“…[9][10][11][12]. Shortly thereafter, the study was generalized to other black hole systems, and some abundant phase structures were discovered, such as the reentrant phase transition, triple point, isolated critical point, and superfluid black hole phase [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (for a recent review see [28] and references therein).Probing the small-large black hole phase transition is an interesting subject. In Ref.[29], the authors found that there is a dramatic change in the slope of the quasinormal modes (QNMs) before and after the black hole's thermodynamic phase transition.…”
mentioning
confidence: 99%
“…In this context, a great deal of interest has recently been devoted to the modified theories of gravity, such massive gravity [2,[22][23][24][25][26][27][28][29][30]. The latter theories spectrum show up a massive spin-2 graviton, providing an explanation of the accelerated expansion of the universe without invoking dark energy.…”
Section: Introductionmentioning
confidence: 99%